2018
DOI: 10.1111/ceo.13345
|View full text |Cite
|
Sign up to set email alerts
|

Post‐surgical versus post‐intravitreal injection endophthalmitis: changing patterns in causative flora

Abstract: S. epidermidis is the most common causative organism. In contrast to other studies, we did not find evidence for an increased odds of Streptococcus spp. endophthalmitis following intravitreal injection. This may in turn reflect guideline-driven changes in practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 22 publications
0
13
0
1
Order By: Relevance
“…These shifting trends suggested that age may influence the microbiological spectrum of endophthalmitis. Previous studies demonstrated that streptococcal infection was associated with poor vision outcome in endophthalmitis [36][37][38]; therefore, a higher proportion of streptococcal infections in children, especially in younger children, merits clinical attention. Antibiotic resistance is a topic of concern worldwide.…”
Section: Discussionmentioning
confidence: 99%
“…These shifting trends suggested that age may influence the microbiological spectrum of endophthalmitis. Previous studies demonstrated that streptococcal infection was associated with poor vision outcome in endophthalmitis [36][37][38]; therefore, a higher proportion of streptococcal infections in children, especially in younger children, merits clinical attention. Antibiotic resistance is a topic of concern worldwide.…”
Section: Discussionmentioning
confidence: 99%
“…(Simunovic et al's study was performed between 2007 and 2010 and Ong et al's study was performed between 2012 and 2017). The authors of this recent study [ 27 ] described a lack of statistically significant difference between both groups, which they justify by the change in causative infection organism, highlighting that S. epidermidis was the most frequent causative organism in endophthalmitis after post-IVI. Between these two studies performed in the same hospital, there was a modification in the protocol management of IVI, more precisely, the implementation of facemask and asking the patient to refrain from talking during the procedures.…”
Section: Discussionmentioning
confidence: 99%
“…The most commonly isolated microorganisms are coagulase-negative staphylococci (40-70%), Staphylococcus aureus (10-17%), streptococci (5-15%), other Gram-positive cocci including enterococci (5%), as well as Gram-negative bacilli (5-10%) including Haemophilus influenzae and Pseudomonas aeruginosa [5][6][7][8]. The microbiologic spectrum of less common forms like post-traumatic or endogenous endophthalmitis is more varied.…”
Section: Definition and Commonly Isolated Microorganismsmentioning
confidence: 99%